GhARF16‐1 modulates leaf development by transcriptionally regulating the GhKNOX2‐1 gene in cotton. Issue 3 (15th October 2020) - He, Peng; Zhang, Yuzhou; Li, Hongbin; Fu, Xuan; Shang, Haihong; Zou, Changsong; Friml, Jiří; Xiao, Guanghui
Summary: The leaf is a crucial organ evolved with remarkable morphological diversity to maximize plant photosynthesis. The leaf shape is a key trait that affects photosynthesis, flowering rates, disease resistance and yield. Although many genes regulating leaf development have been identified in the past years, the precise regulatory architecture underlying the generation of diverse leaf shapes remains to be elucidated. We used cotton as a reference model to probe the genetic framework underlying divergent leaf forms. Comparative transcriptome analysis revealed that the GhARF16‐1 and GhKNOX2‐1 genes might be potential regulators of leaf shape. We functionally characterized the auxin‐responsive factor ARF16‐1 acting upstream of GhKNOX2‐1 to determine leaf morphology in cotton. The transcription of GhARF16‐1 was significantly higher in lobed‐leaved cotton than in smooth‐leaved cotton. Furthermore, the overexpression of GhARF16‐1 led to the up‐regulation of GhKNOX2‐1 and resulted in more and deeper serrations in cotton leaves, similar to the leaf shape of cotton plants overexpressing GhKNOX2‐1 . We found that GhARF16‐1 specifically bound to the promoter of GhKNOX2‐1 to induce its expression. The heterologous expression of GhARF16‐1 and GhKNOX2‐1 in Arabidopsis led to lobed and curly leaves, and a genetic analysis revealed that GhKNOX2‐1 is epistatic to GhARF16‐1 in Arabidopsis, suggesting that the GhARF16‐1 and GhKNOX2‐1 interaction paradigm also functions to regulate leaf shape in Arabidopsis . To our knowledge, our results uncover a novel mechanism by which auxin, through the key component ARF16‐1 and its downstream‐activated gene KNOX2‐1, determines leaf morphology in eudicots.